(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article systemically analyzes the emergence, historical development stages, and specific evolutionary aspects of the border guarding system. It explores ancient natural barriers and magnificent defense walls (The Great Wall of China, Kanpirak Wall), Amir Temur’s advanced border security strategy during the Middle Ages, as well as the delimitation and demarcation processes of the Modern era. Furthermore, the role of digital technologies, artificial intelligence, drones, and biometric control systems in contemporary border defense is highlighted. The article aims to study the historical experience and modern trends of the border protection system.